PENDEKATAN HOLISTIK DALAM OPTIMALISASI PERSIAPAN SISWA SMKS YABHINKA UNTUK MAGANG KE JEPANG : PENERAPAN ANGGARAN SMK PUSAT KEUNGGULAN - Sembiring, Evi Dora; Susilawati, Deti; Anggriawan, Muhammad Angga; Pertiwi, Sari Putri; Handayani, Novi; Samsinar, Ade (Nindikayla Institute, 2025)
Internship preparation activities to Japan are one of the activities of SMK PK (Center of Excellence) approved by the Ministry of Education, through the SMK PK budget. For Vocational High School (SMK) students, the internship program to Japan is an opportunity to improve work skills and get to know advanced culture and technology. However, students' readiness to face the challenges of this international internship is still a major obstacle. This article discusses the importance of a holistic approach in optimizing the preparation of SMK students for internships in Japan, which involves mastery of Japanese, understanding work culture, developing technical and non-technical skills, and physical and mental training. This holistic approach combines various aspects of education and self-development as a whole, so that students can adapt more easily and succeed in the internship program. In addition, collaboration between SMK, companies, and related institutions is needed to ensure effective implementation. Thus, this approach is expected to be able to create students who are ready to face global challenges and have superior competencies